The Mood-Residue Structure in “Learn English with Taylor Swift Talk Show” - Aminatus Sholehah; Eka Fanti Sulistiyaningsih (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
Functional grammar is a widely used systemic functional grammar. There are three strands of meaning in clauses. They are ideational, textual, and interpersonal. This research focuses on the kind of clause as exchange. So, the researcher uses interpersonal meaning. Interpersonal meaning consists of mood and residue. And we use interpersonal meaning study in our daily activity. The design of this research is descriptive qualitative. This research used spoken data collected from analyzing “Learn English with Taylor Swift Talk Show”. Based on analyzing the data, the result shows that all of the clauses in the talk show use mood structure with the form of subject + infinite / finite + subject. And the residue structure shows that not each clause uses the form of predicate, complement, and adjunct. Based on the data analysis, it is found out that the mood system consists of indicative and imperative. The indicative covers declarative and interrogative. There were 154 declarative clauses. Then, 8 clauses are included in interrogative clauses. It consists of 3 polar clauses and 5 wh-q clauses. The residue structure in the transcript of “Learn English Online with Taylor Swift Talk Show” consists of predicate, complement, and adjunct